Good University Governance: Budget Accountability And The Demarcation Of Legal Risks In Public Universities - Ari Yunus Hendrawan (Mandalika Institute, 2026)
Good University Governance (GUG) constitutes a fundamental framework for ensuring financial accountability and legal compliance in public universities. Although previous studies have extensively examined financial accountability and internal control in higher education, limited attention has been devoted to the legal risk demarcation between procedural administrative errors and corruption offenses arising from dysfunctional treasury systems during institutional crises. This study addresses this gap by analyzing the implementation of the principles of segregation of duties and functional accountability while examining the legal boundaries between administrative maladministration and criminal liability in budget management within a public university postgraduate program during the 2018–2022 fiscal years. Employing a qualitative empirical juridical (socio-legal) case study, data were collected through semi-structured interviews with eleven key informants, organizational observations, and documentary analysis of forensic audit reports and state treasury records. The findings indicate that the prolonged dysfunction of officially designated treasury officers resulted in the informal delegation of financial responsibilities to contract-based staff, creating serious governance failures. These failures were manifested in manipulated financial documents, counterfeit official stamps, and double-funding practices involving personal bank accounts, demonstrating the existence of criminal intent rather than mere procedural irregularities. The novelty of this study lies in integrating Good University Governance with contemporary administrative and criminal law perspectives to establish a legal risk demarcation framework distinguishing maladministration from corruption offenses. The study contributes theoretically by extending governance-based legal accountability in public universities and practically by recommending mandatory cashless transactions, integrated digital payment systems, and stricter segregation of duties to strengthen financial accountability and prevent corruption.